Composite materials development from recyclable dry fraction of household solid wastes. (October 2015) - Sánchez, R.; Betancourt, E.; Camero, S.; Franco, F.; Molina, A.
Abstract : A procedure was developed to manufacture polymer-based composite (PMC) materials from recyclable dry fraction of household solid wastes. They were collected and each component underwent size reduction, drying, sieving and was separated into two size fractions. Subsequently, they were mixed using a statistically determined proportion. Mixtures werehot pressed to form cylindrical compacts and characterised by following standardised procedures. Results indicate that the procedure was able to produce a particulate PMC, which constitutes an interesting choice to utilise domestic solid wastes; minimising, their handle and deposition problems. In terms of mechanical properties, it seems that the new material could be used in different applications such as furniture, chairs, tables, desks or construction materials without structural compromises such as: decking, flooring, fencing, wall panels, etc.